2006
DOI: 10.1177/0163443706059295
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic transformations: youth, global media and indigenous culture in Malta

Abstract: The article explores the impact of global commercial media on young people’s developing perceptions of their own cultural identity. It works from the premise that local cultures are not so much getting replaced by ‘global culture’ as inflecting it by coexisting with it. The discussion draws on data collected in the course of focus group interviews with young adults living in the Mediterranean island of Malta, in order to stress the specificity with which young people from different cultural contexts consume gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Losses relative to the local culture and homogenization were also articulated by McCarty (2003) as the diminishment of linguistic and cultural diversity due to processes of globalization. This concern was observed by Grixti (2006), who found that higher SES youth from Malta gravitated toward foreign values (e.g., commercialism) rather than local (a trend not observed among their low SES counterparts).…”
Section: Risks Of Globalization For Identity Formationmentioning
confidence: 91%
See 4 more Smart Citations
“…Losses relative to the local culture and homogenization were also articulated by McCarty (2003) as the diminishment of linguistic and cultural diversity due to processes of globalization. This concern was observed by Grixti (2006), who found that higher SES youth from Malta gravitated toward foreign values (e.g., commercialism) rather than local (a trend not observed among their low SES counterparts).…”
Section: Risks Of Globalization For Identity Formationmentioning
confidence: 91%
“…Writers have begun to address the outcomes or impacts of globalization on child and adolescent development, including both risks and prospects or opportunities (e.g., Kaufman, Rizzini, Wilson, & Bush, 2002;McDade & Worthman, 2004;Thompson, 2002). Of some interest have been the entanglements of local, national, and global strands relative to child development as well as the experiences of those who are marginalized (Arnett, 2002;Grixti, 2006;Kaufman et al, 2002). Globalization is particularly germane to adolescents due to their keen interest in and accessibility to global informational sources (Arnett, 2002;Jensen, 2003;Schlegel, 2000) with significant implications for identity formation (Arnett, 2002;Dolby, 1999;Edgecombe, 2004;Fairweather, 2006).…”
Section: Globalization and Identity Formationmentioning
confidence: 99%
See 3 more Smart Citations